Profile Screening of Differentially Expressed lncRNAs of Circulating Leukocytes in Type 2 Diabetes Patients and Differences From Type 1 Diabetes - Lv, Jianyi; Liu, Yihan; Cui, Jia; Fang, Hongjuan; Wu, Ying; Zhu, Xiao; Guo, Meng; Li, Changlong; Dou, Jingtao; Chen, Zhenwen; Du, Xiaoyan (Frontiers in Endocrinology, 2022)
Long noncoding RNAs (lncRNAs) have been reported to have multiple functions and can be used as markers of various diseases, including diabetes. This study was conducted to determine the lncRNA profile in leukocytes from patients with type 2 diabetes (T2D). Differential expression of lncRNAs in T2D and type 1 diabetes (T1D) was also examined. RNA sequencing was performed in a critically grouped sample of leukocytes from T2D patients and healthy persons. A total of 845 significantly differentially expressed lncRNAs were identified, with 260 downregulated and 585 upregulated lncRNAs in T2D. The analysis of functions of DE-lncRNA and constructed co-expression networks (CNC) showed that 21 lncRNAs and 117 mRNAs harbored more than 10 related genes in CNC. Fourteen of 21 lncRNAs were confirmed to be significantly differentially expressed was detected by qPCR between the T2D and control validation cohorts. We also identified a panel of 4 lncRNAs showing significant differences in expression between T1D and T2D. Collectively, hundreds of novel DE-lncRNAs we identified in leukocytes from T2D patients will aid in epigenetic mechanism studies. Fourteen confirmed DE-lncRNAs can be regarded as diagnostic markers or regulators of T2D, including 4 lncRNAs should distinguish T1D and T2D in clinical practice to avoid misdiagnosis.